SOLID-PHASE IMMUNOASSAY USING A FLOW CYTOMETER - QUANTITATIVE AND QUALITATIVE DETERMINATION OF PROTEIN ANTIGENS AND A HAPTEN - KIM, K; HAN, MY; YOON, DY; CHO, B; CHOI, MJ; CHOE, IS; CHUNG, TW (ELSEVIER SCIENCE BV, 1992)
A fluoroimmunoassay employing a flow cytometer as the fluorescence-detecting device is described. Three kinds of antigens, murine immunoglobulin (Ig), human chorionic gonadotropin (hCG) and progesterone were chosen as examples of the assay using fluorescein-labeled antibodies. Cyanogen bromide-activated agarose beads were used as solid-phase supporters. The flow cytometric immunoassay was applied to both qualitative and quantitative analyses; determination of murine Ig isotypes, quantitative determination of Ig, hCG and a hapten, progesterone. This assay produced very reproducible and less-fluctuating data since thousands of particles in the assay were collected and processed to produce a single value for fluorescence intensities. Furthermore, the working range of the assay in terms of antigen concentration was much broader than that of enzyme immunoassay. Therefore, we believe that microparticles like agarose beads could be useful solid-phase supporters in immunoassays, and the flow cytometer could provide a reliable alternative to the fluorescence-detecting device in immunoassay.